Variations in training of surgical oncologists: Proposal for a global curriculum. Issue 6 (June 2016) - Are, C.; Caniglia, A.; Malik, M.; Cummings, C.; Lecoq, C.; Berman, R.; Audisio, R.; Wyld, L.
Abstract: Background: The global cancer burden is predicted to rise significantly over the next few decades. While there are several barriers to providing optimal cancer care on the global stage, some are related to the absence of an adequately trained workforce. This could be attributed in part to the significant global variations in the training of surgical oncology professionals. There are currently no published data mapping the training pathways for surgical oncologists for all countries in the world. The aims of this descriptive article are to report on the training paradigms in surgical oncology for all countries in the world, and to correlate the influence of economic standing on these training paradigms. Materials and methods: The training paradigms for all countries in the world were analyzed and categorized on the basis of the six World Health Organization geographic regions and economic standing stratified by the Human Development Index. Results: Data on the training paradigms were obtained for 174 countries from a total of 211 (82%). We noted extremely significant and concerning variations in the length, availability and structure of training paradigms depending on the geographic region and economic standing. Conclusions: The results of our study demonstrated significant global variations in the training paradigms of surgical oncologists. These variations call for a global curriculum which has been developed by the Society of Surgical Oncology and the European Society of Surgical Oncology. It is hoped that this curriculum will serve a role in streamlining education to tackle the rising global cancer burden. Abstract : The results of this study demonstrated significant global variations in surgical oncology training. These results call for a global curriculum in surgical oncology which has been developed by the Society of Surgical Oncology and the European Society of Surgical Oncology.